Production of Bacillus subtilis-fermented red alga Porphyra dentata suspension with fibrinolytic and immune-enhancing activities. Issue 6 (3rd June 2014) - Lin, Hong-Ting Victor; Hwang, Pai-An; Lin, Tzu-Chun; Tsai, Guo-Jane
Abstract: The fermented marine alga Porphyra dentata suspension was tested for its fibrinolytic and immune-enhancing activities. An isolated Bacillus subtilis N2 strain was selected for its fibrinolytic activity on fibrin plates. After investigating the effects of biomass amounts of P. dentata powder in water, various additives including sugars, nitrogen-containing substances, lipids and minerals, and cultural conditions of temperature and agitation in flask, the highest fibrinolytic activity in the cultural filtrate was obtained by cultivating N2 strain in 3% (w/v) P. dentata powder suspension containing 1% peanut oil at 37 °C, 150 rpm for 48 h. A fermentor system was further established using the same medium with controlled pH value of 7.0 at 37 °C, 150 rpm, 2.0 vvm for 48 h for the best fibrinolytic activity. The fermented product also showed its immune-enhancing activity by increasing cell proliferation and stimulating the secretion of IL-1β, IL-6, and TNF-α in J774.1 cells. Graphical abstract: : Fibrinolytic Activity of the Culture Filtrate of B. subtilis N2. 10 μL of culture filtrate of B. subtilis N2 in TSB at 37°C for 24 h was applied to a fibrin plate for observation of clear zone. The commercial TSB medium without inoculum was served as the control.